The evaluation of recognize of clinical factors and microscopyexamination vaginal discharge in vaginal candidias diagnostic among the women who reffered to kohasht health –medical center in 2011 - Dolatian, Mahrokh; Ebrahimi, Frzaneh; Alavi Majd, Hamid (Advances in Nursing & Midwifery, 2014)
Abstract AbstIntroduction: The reproductive system infections are most common womens reasons for repetitive refers to gynecological clinic and the second problem is vulvovaginal candidiasis. since, distribution of patients and clinical signs may cause the wrong diagnose and treatment , in this study clinical signs and examination microscopy and vaginal discharge were compared. Method: In this descriptive study that has done among 18-44 married women years with complain from vaginal itching or irritation (july-may 2011). After diagnose the vaginite associate of patients complains and rigest the clinical signs, three sampling were done from every women. Two of them for wet mount with saline /KOH 10% and the other sample for sending to lab to culture purpose(golden standard test). data analysis was performed by spss 17 soft ware. Result: Among the factors that evaluate the most sensitivity belong to vulval erythema (89/1%) and the less sensitivity belong to cottage discharge(74/3%) and in the microscopic examination, the most specificity(100%) and the less specificity belong to themselves in vaginal candidiases diagnose between studied factors. Conclusion: Using the lab method (culture) and microscopic study on vaginite diagnose. Keyword: candida vaginitis, microscopy examination, candidiasis REFERENCES Ali B Sh,Tohidi A(2000)” Prevalence of candida vaginitis among symptomatic patiets in kerman”. The Journal of Qazvin University of Medical Science. (13). 42-48 Bansal KM, Singh K and Bhatnagar S (2001)” Prevalence of lower RTI among married female in the reproductive age group(15-45). Health and population. 24(3)157-163. Berek JS & Novak E. (2007). Berek & Novak’s Gynecology. 14th ed. Philadelphia, Lippincott Williams & Wilkins. 542-547. Buyukbayrak EE, Kars B, Karageyim karsidag AY, Ilkay karadenis B, Kaymas O, Geneer S(2010)”Diagnosis of vulvovaginitis: comparison of clinical and microbiological diagnosis”. Archive of Gynecology and Obstetrics. 282(5): 515-519. Ehrstrom S, Kornfeld D, Rylander E (2007)” Perceived stress in women with recurrent vulvovaginal candidiasis”. Jurnal of Psychosomatic Obstetrics and Gynecology. 28(3)169-176 Kariman N, Shafai Z, Afrakhte M, Valai N, Ahmadi M(2002)”Comparative study of traputic effects of fluconazole and clotrimazole on candida vaginitis”. Jornal Behbood. 6(13): 9-16 Martinez RCR, Franceschini SA, Patta MC, Quintana SM, Candido RC, Frreira ECP and etal(2009)”Improved treatment of vulvovaginal candidiasis with fluconazole plus probiotic lactobacillus rhamnosus GR-1 and lactobacillus reuteri RC-14”. Letters in Applied Microbiology. 48(3): 269-274. Moreira D, Paula CR(2006)” Vulvovaginal candidiasis”. International Journal Gynecology and Obestetrics. 92: 266-267. Ryan KJ, Berkovitz R, Robert L, Ryan BJ. (1999). Kistner’s gynecology. 5th ed. Medical Publisher Inc. 476-480 Sobel DJ(2007)” Vulvovaginal candidosis”. Lancet. 396(9577): 1961-1971.